STRATEGI GURU DALAM MANAJEMEN KELAS UNTUK MENCIPTAKAN SUASANA BELAJAR YANG KONDUSIF DI KELAS III MADRASAH IBTIDAIYAH AL-BIRRA KOTA PEKANBARU - Nisya Frasetia; Sakban; Deprizon; Salman; Cici Saputri (Jurnal Payung Sekaki : Kajian Keislaman, 2025)
This research is motivated by the problem of a less conducive learning atmosphere in class III of MI Al-Birra Pekanbaru City, such as crowded students, narrow classes, and lack of focus in learning. The purpose of this study is to describe teacher strategies in classroom management that can create an orderly and comfortable learning atmosphere. This study uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The results of the study show that teachers apply strategies such as compiling class rules together, flexible seating arrangements, using ice breakers, as well as active learning and individual approaches. Teachers also establish positive communication with students, involve them in setting class rules, and resolve conflicts peacefully. School support is seen in the form of supervision, training, and provision of learning facilities. The use of learning media, including digital technology, also supports the creation of a conducive class. The conclusion of this study is that effective classroom management strategies play an important role in creating a comfortable, orderly learning atmosphere that supports active student participation, and has a positive impact on learning outcomes.